EDUCATING CHILDREN IN THE DIGITAL AGE - Lubis, Sofni Indah Arifa; Rahman, Mhd. Habibu; Yanti, Nursaida (Proceeding International Seminar of Islamic Studies, 2023)
This article explores critically the early childhood teachers` perspectives on the changes in the nature of childhood in this digital era. The rapid development of the digital era nowadays unquestionably has already changed children`s lives and it affected the teaching and learning activities. Both early childhood children and early childhood teachers grow and develop naturally with the development of digitalization. Digital technologies are bringing opportunities for learning and education for children but at the same time changing them into more personal people and less attached to the real world. Preparing the children with a set of skills to be able to succeed in this digital era is one of the early childhood teachers` responsibilities. To document this, 15 early childhood teachers were interviewed. The results were discussed in two terms. First, the early childhood teachers acknowledge the changing nature of childhood in this digital era. Second, the strong commitment of the early childhood teachers in arranging a fun yet creative indoor and outdoor learning activities for the children